Lukrecja – wzór dla Rzymianek. Historia niezbyt słodka - Miazek-Męczyńska, Monika (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The article presents the story of Lucrece, legendary heroine and noble wife of Lucius Tarquinius Collatinus, whose suicide was presented many times in the ancient Roman and Renaissance literature by historiographers and poets. The author compares few versions of Lucrece’s story focusing on her virtues (like castitas, obstinata pudicitia, decus muliebris) that became canonical features characterising the Roman matrona.